Safe Sleep Knowledge and Use of Provided Cribs in a Crib Delivery Program - Engel, Matthew; Ahlers-Schmidt, Carolyn R.; Suter, Bonita (Kansas Journal of Medicine, 2019)
Introduction. Risk of infant sleep-related death can be reduced through safe sleep practices. Barriers to infant safe sleep have been mitigated through education and crib distribution, however, previous studies have not explored whether distributed cribs are put to use. Methods. In a rural Michigan county, the Great Start Sleep Initiative supplied cribs and education shortly after infant birth to families with high-risk of infant mortality, as assessed through comprehensive interviews with families by program staff. Participant knowledge was evaluated using structured pre- and post-assessments before and after education. Further, a home visit was conducted to evaluate the infant’s sleeping environment. Data from the program, collected between January 2012 and December 2014, were evaluated. Results. Cribs and concomitant education were delivered to 75 caregivers. Knowledge of safe sleep practices increased significantly at follow-up with 67 caregivers (89%) affirming back positioning, 68 (91%) endorsing removal of unsafe items or soft objects, such as blankets, from the sleeping area, and 42 (56%) renouncing bedsharing. At the home visit, 74 caregivers (99%) were using a crib to put their infant down to sleep, 70 (93%) were using the provided crib, and 67 (89%) had no unsafe items in the child’s sleeping area. Conclusion. Providing education to high-risk mothers resulted in improved safe sleep knowledge and provided cribs are used in these homes. KS J Med 2017;10(3):59-61.